Applicability of an immersive virtual reality system to assess egocentric orientation of older adults - Silva, Juliana Magalhães da; Santos, Michelle Didone dos; Costa, Raquel Quimas Molina da; Moretto, Emerson Galves; Viveiro, Larissa Alamino Pereira de; Lopes, Roseli de Deus; Brucki, Sonia Maria Dozzi; Pompeu, José Eduardo (Arquivos de Neuro-Psiquiatria, 2023)
Background Spatial orientation is a cognitive domain frequently compromised in patients with Alzheimer disease (AD) and may be one of its first clinical manifestations. Some studies have shown that allocentric integration with egocentric spatial information seems to be impaired in this pathology. There is no consensus on how best to assess spatial orientation and traditional tests lack ecological validity, but, recently, virtual reality (VR) has provided new opportunities for this assessment.Objectives To analyze the applicability and stability of an immersive virtual task developed to assess spatial orientation, the Spatial Orientation in Immersive Virtual Environment Maze Test (SOIVET-Maze) in older adults with and without mild cognitive impairment.Methods Forty-three older adults were included in the study, 24 without cognitive impairment and 19 with mild cognitive impairment. Applicability was assessed by the Witmer and Singer Sense of Presence Questionnaire and a questionnaire for adverse events of cybersickness. To assess stability, participants were assessed twice with an interval of 7 to 14 days, and the intraclass correlation coefficient was calculated between visits. The t test or the Mann-Whitney test was used to compare applicability and stability between groups.Results There was no significant difference between the groups regarding applicability. A strong correlation between the first and second day of testing was found in the mild cognitive impairment group.Conclusion The SOIVET-Maze task showed excellent applicability and good stability, favoring its clinical application for the evaluation of spatial orientation in older adults.
Keywords: Orientation, Spatial; Virtual Reality; Aged; Reproducibility of Results; Data Accuracy